Analysis Quality Control in Project Development Warehouse PT Santos Jaya Abadi Using the Process Decision Program Chart Method - Yohanes Usman Nandyanto; Michella Beatrix; Masca Indra Triana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Construction project must have quality control to guatantee safety worker. However, even though technical specifications have been prepared, deviations in quality during construction project implementation always occur, so the great of the building does now not comply with the satisfactory requirements which have been set and reasons the low quality of human resources in the construction global. This research began with data collection through the process decision program chart method and questionnaire method, distributed to project warehouse PT Santos Jaya Abadi. The collected data questionnaires were analyzed using Process Decision Program Chart Method dan Microsoft Excel. The analysis quality control and analysis risk show that quality control effective and implemented in project contruction. The result of structure work such as beam and column have the same percentage of 76%, floor plate has a percentage of 72%. While on structure work beam has risk level value 7.49, column with a value of 7.42, floor plate with a value of 6.43. , floor plate structure work with a value of 6.43.